Catching the second wave: clinical characteristics and nosocomial infection rates in major trauma and orthopaedic patients during the COVID-19 pandemic. (19th August 2021) - Ajayi, Bisola; Trompeter, Alex J.; Umarji, Shamim; Saha, Priyanshu; Arnander, Magnus; Lui, Darren F.
Abstract : Aims: The new COVID-19 variant was reported by the authorities of the UK to the World Health Organization (WHO) on 14 December 2020. We aim to describe the clinical characteristics and nosocomial infection rates in major trauma and orthopaedic patients comparing the first and second wave of COVID-19 infection. Methods: A retrospective analysis of a prospectively collected trauma database was reviewed at a level 1 major trauma centre from 1 December 2020 to 18 February 2021 looking at demographics, clinical characteristics, and nosocomial infections and compared to our previously published first wave data (26 January 2020 to 14 April 2020). Results: From 1 December 2020 to 18 February 2021, 522 major trauma patients were identified with a mean age of 54.6 years, and 53.4% (n = 279) were male. Common admissions were falls (318; 60.9%) and road traffic accidents (RTAs; 71 (13.6%); 262 of these patients (50.2%) had surgery. In all, 75 patients (14.4%) tested positive for COVID-19, of which 51 (68%) were nosocomial. Surgery on COVID-19 patients increased to 46 (61.3%) in the second wave compared to 13 (33.3%) in the first wave (p = 0.005). ICU admissions of patients with COVID-19 infection increased from two (5.1%) to 16 (20.5%), respectively (p = 0.024). Second wave mortality was 6.1% (n = 32) compared to first wave of 4.7% (n = 31). Cardiovascular (CV) disease (35.9%; n = 14); p = 0.027) and dementia (17.9%; n = 7); p = 0.030) were less in second wave than the first. Overall, 13 patients (25.5%) were Black, Asian and Minority ethnic (BAME), and five (9.8%) had a BMI > 30 kg/m 2 . The mean time from admission to diagnosis of COVID-19 was 13.9 days (3 to 44). Overall, 12/75 (16%) of all COVID-19 patients died. Conclusion: During the second wave, COVID-19 infected three-times more patients. There were double the number of operative cases, and quadruple the cases of ICU admissions. The patients were younger with less dementia and CV disease with lower mortality. Concomitant COVID-19 and the necessity of major trauma surgery showed 13% mortality in the second wave compared with 15.4% in the first wave. In contrast to the literature, we showed a high percentage of nosocomial infection, normal BMI, and limited BAME infections. Cite this article: Bone Jt Open  2021;2(8):661–670.